Hyperspectral Image Classification Using Dimensionality Reduction Deep Networks - Kavitha, D.; Shobana, S.; Rajkumar, S.; Reddy, Ganta Raghotham; Babu P., Ramesh; Mukherjee, Papiya (International Journal of Intelligent Systems and Applications in Engineering, 2023)
In this research, we apply a convolutional neural network (CNN) to three publicly available hyperspectral datasets to determine which of these four models is the most effective when it comes to reducing the number of dimensions. The findings demonstrate that the models have a higher rate of classification accuracy on the smaller datasets when compared to the other techniques. It would appear from the observations that employing SuperPCA results in an overall improvement in the classifier level of effectiveness.